Kafkaesque institutions at the base of the pyramid. Issue 17 (21st November 2016) - Khare, Apoorv; Varman, Rohit
ABSTRACT: Impelled by neo-liberal ideology, base-of-the-pyramid (BOP) and subsistence market discourses have put emphases on markets, profits and entrepreneurialism. Because of this ideological mooring, there is a marginal understanding of the role of the State and its impact on the poor in these discourses. Franz Kafka's work provides a critical perspective on the role of the State in BOP or subsistence settings. This ethnographic study in India examines transactions related to land and highlights the Kafkaesque nature of the State. The institutional setting is fraught with Kafkaesque elements such as inaccessible and indecipherable legality, abusive power relations and alienation of subaltern subjects. It further shows that the illicit character of the State is an important reason for illegal practices in subaltern settings.